The Bioassay Guided Screening of Cryptolepis Extracts for Onward Synthesis of Nano Ferrites - Hafza Murtaza; Aasia Sikander; Umema Murtaza; Ashir Masroor; Filza Ghafoor (Newinera Publisher, 2021)
In this study, various leaves and stem organic extracts were prepared using the solvents viz., n-hexane, ethyl acetate, ethanol and water, separately. Different phytochemical test for alkaloids, carbohydrates, oils, amino acids and others were performed to determine their presence in the extracts. These plant extracts were used for screening of sample via UV and HPLC techniques to compare the wavelength and absorbance, and retention time on chromatogram by extracts, respectively. The surface properties and size of nickel-zinc nano ferrites were evaluated by Energy-dispersive X-ray spectroscopy (EDX) and Scanning Electron Microscopy (SEM). The former, showed the presence of nickel (Ni) and zinc (Zn) weighing 4.27⁒ of N ,6.89⁒ of C and 35.5⁒ of O in the sample which confirmed the presence of nano ferrites in leaves and stem of C. buchanani.